L’identité amazighe aux Canaries : l’historiographie des origines - Josué Ramos-Martín (L’Année du Maghreb)
The inhabitants of the Canary Islands, located off the African coast, have been mentioned in many narratives about Berber history and identity. These however, are not often studied with a view of uncovering the causes of this link or how it came about. This proposes an analysis of how historiography has included Berber/Amazigh components in a story of origins. In this paper the author describes the genealogical and chronological development of this historiographical process, emphasizing how the implementation of different discourses made sense for community ownership. Finally, we assess the consequences of this process on Canary Islanders identity.